THE IMPACT OF AIR POLLUTION ON RESPIRATORY HEALTH: ASSESSING THE LONG-TERM EFFECTS AND DEVELOPING PREVENTIVE STRATEGIES - Maged Abdulaziz Alzoman, Abdullah Saud Alyousef, Naif Madallah Alanazi, Mohammed Nawaf Alanzi, Mahdi Ali Alhelal, Yasseen Jafar Hussein Alabdrabalnebi, Meshal Mohammed Alqahtani, Abdullah Ebrahim Almadhari,,; Saeed Fayes Saeed Aldwasari, Yasser Emad Moqbil Alharbi , (Chelonian Research Foundation, 2022)
With the increasing worldwide awareness of air pollution, there is a growing need to provide evidence-based suggestions for measures to reduce its effect. Public policy plays a crucial role in mitigating air pollution, but individuals may also decrease their exposure via personal decisions. Empirical data strongly supports the idea of restricting outdoor physical activity on days with high air pollution levels and in close proximity to sources of air pollution. It is also advisable to minimize exposure to pollutants from roadways when commuting, make use of air quality warning systems to schedule activities, and use facemasks when necessary. Additional tactics include refraining from using solid fuels for cooking, ensuring proper ventilation and isolation of cooking spaces, and employing transportable air purifiers equipped with high-efficiency particle air filters. We provide specific suggestions to aid medical professionals and public health officials in advising individuals on personal strategies to reduce the impact of air pollution. However, it is important to note that further research is necessary to thoroughly establish and validate interventions that effectively improve respiratory health in this setting. Keywords: air pollution, respiratory health, medical professional, long-term effects.